Building the Framework for Standardized Clinical Laboratory Reporting of Next-generation Sequencing Data for Resistance-associated Mutations in Mycobacterium tuberculosis Complex. (18th March 2019) - Tornheim, Jeffrey A; Starks, Angela M; Rodwell, Timothy C; Gardy, Jennifer L; Walker, Timothy M; Cirillo, Daniela M; Jayashankar, Lakshmi; Miotto, Paolo; Zignol, Matteo; Schito, Marco
Abstract: Tuberculosis is the primary infectious disease killer worldwide, with a growing threat from multidrug-resistant cases. Unfortunately, classic growth-based phenotypic drug susceptibility testing (DST) remains difficult, costly, and time consuming, while current rapid molecular testing options are limited by the diversity of antimicrobial-resistant genotypes that can be detected at once. Next-generation sequencing (NGS) offers the opportunity for rapid, comprehensive DST without the time or cost burden of phenotypic tests and can provide useful information for global surveillance. As access to NGS expands, it will be important to ensure that results are communicated clearly, consistent, comparable between laboratories, and associated with clear guidance on clinical interpretation of results. In this viewpoint article, we summarize 2 expert workshops regarding a standardized report format, focusing on relevant variables, terminology, and required minimal elements for clinical and laboratory reports with a proposed standardized template for clinical reporting NGS results for Mycobacterium tuberculosis . Abstract : An expert consensus process was used to develop a standardized framework for reporting and communicating clinically relevant next-generation sequencing data from Mycobacterium tuberculosis for guiding drug treatment options.